2017
DOI: 10.19030/jabr.v33i5.10016
|View full text |Cite
|
Sign up to set email alerts
|

Improving The Compliance With Accounting Standards Without Public Accountability (SAK ETAP) By Developing Organizational Culture: A Case Of Indonesian SMEs

Abstract: In Indonesia’s economy SMEs have significant contribution to GDP and labor employment. On the other hand, SMEs still have substantial problems. One of them is related to capital insufficiency due to limited access of SMEs to financial institutions. This limitation may be caused, among other things, by the fact that SMEs’ financial statements have not complied with Accounting Standards without Public Accountability (SAK ETAP). The study aims at identifying antecedents of SAK ETAP implementation as well as formu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 28 publications
1
17
0
5
Order By: Relevance
“…Descriptive analysis is used to describe and describe the variables in this study. Descriptive statistical analysis in this study includes the mean, maximum, minimum and standard deviation (Yanto et al, 2017). The results of the descriptive statistical analysis can be seen in Table.1 below: The results showed that the average Return on Equity value of 0.03 in the 2015-218 time span.…”
Section: Descriptive Statistical Analysismentioning
confidence: 87%
“…Descriptive analysis is used to describe and describe the variables in this study. Descriptive statistical analysis in this study includes the mean, maximum, minimum and standard deviation (Yanto et al, 2017). The results of the descriptive statistical analysis can be seen in Table.1 below: The results showed that the average Return on Equity value of 0.03 in the 2015-218 time span.…”
Section: Descriptive Statistical Analysismentioning
confidence: 87%
“…Thus, the research data can be said to be normally distributed. With a descriptive analysis design, correlation, and path analysis to test exogenous, endogenous and mediating or intervening variables (Yanto et al, 2017). Model testing is carried out using the goodness of fit referring to the value of six indexes, namely Chi Squared, Goodness of Fit Index (GFI), Goodness of Fit Index (AGFI), Root Mean Square of Approximation (RMSEA), Normed Fit Index (NFI), and Comparative Fit Index (CFI), and CMIN / df ( (Lleras, 2005;Albright & Park, 2009;Ghozali, 2017;Yanto et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…Haryani (2012) found that MSMEs are still not familiar with preparing financial reports based on SAK-ETAP even though the SAK-ETAP has been implemented in January 2010. There are obstacles in generating standardized financial reports such as inappropriate infrastructures of accounting, human resources, and education (Yanto et al, 2017) while the external factors are lack of participation of government institutions and SMEs (Ermawati, 2018).…”
Section: Perception Of Standard Of Accounting Financial Entity Without Public Accountability (Sak-etap) (This Code Can Be Described As Inmentioning
confidence: 99%